Multiphase Assembly of Small Molecule Microcrystalline Peptide Hydrogel Allows Immunomodulatory Combination Therapy for Long‐Term Heart Transplant Survival. Issue 38 (18th August 2020) - Majumder, Poulami; Zhang, Yichuan; Iglesias, Marcos; Fan, Lixin; Kelley, James A.; Andrews, Caroline; Patel, Nimit; Stagno, Jason R.; Oh, Byoung Chol; Furtmüller, Georg J.; Lai, Christopher C.; Wang, Yun‐Xing; et al.
Abstract: Combination therapies that target multiple pathways involved in immune rejection of transplants hold promise for patients in need of restorative surgery. Herein, a noninteracting multiphase molecular assembly approach is developed to crystallize tofacitinib, a potent JAK1/3 inhibitor, within a shear‐thinning self‐assembled fibrillar peptide hydrogel network. The resulting microcrystalline tofacitinib hydrogel (MTH) can be syringe‐injected directly to the grafting site during surgery to locally deliver the small molecule. The rate of drug delivered from MTH is largely controlled by the dissolution of the encapsulated microcrystals. A single application of MTH, in combination with systemically delivered CTLA4‐Ig, a co‐stimulation inhibitor, affords significant graft survival in mice receiving heterotopic heart transplants. Locoregional studies indicate that the local delivery of tofacitinib at the graft site enabled by MTH is required for the observed enhanced graft survival. Abstract : Combination therapies targeting pathways in immune rejection of transplants hold promise for restorative surgery patients. Microcrystalline tofacitinib hydrogel (MTH) can be syringe‐injected directly to the grafting site to locally deliver tofacitinib, a potent JAK1/3 inhibitor. A single application of MTH, in combination with systemic CTLA4‐Ig, a co‐stimulation inhibitor, affords significant graft survival in mice receiving heterotopic heart transplants.